(untitled) (Applied Biological Research, 2019)
The present study examined the morphology, anatomy and palynological characters of eight species of Dioscorea growing in Meghalaya (India). A total of 128 characters of Dioscorea species were assessed using principal component analysis (PCA) and cluster analysis methods. The first four principal components indicated 79.42% of the total observed variability. Characters with discriminating values were stem twinning direction, position of leaves, leaf apex shape, petiole colour, male flower colour, male floral bracteoles shape, inner tepal shape of male flower, style shape, fruit shape, seed shape, seed wing position, vascular bundle in outer ring, number of paracytic stomata, breath of stomata, width of pollen aperture and orbicule diameter. The cluster analysis clearly separated the species based on their close association.